2015
DOI: 10.1021/jacs.5b10776
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characterization of Crystalline Supramolecular Rotors Assembled through Halogen Bonding

Abstract: A modular molecular kit for the preparation of crystalline molecular rotors was devised from a set of stators and rotators to gain simple access to a large number of structures with different dynamic performance and physical properties. In this work, we have accomplished this with crystalline molecular rotors self-assembled by halogen bonding of diazabicyclo[2.2.2]octane, acting as a rotator, and a set of five fluorine-substituted iodobenzenes that take the role of the stator. Using variable-temperature (1)H T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
61
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 39 publications
0
61
1
1
Order By: Relevance
“…This is duet ot he well-known fast rotation of the DABCO unit alongi ts pseudo-three-fold axis, which is associated with av ery low activatione nergy. [30][31][32] Such motion cannotb e frozen at the lowest achievable NMR temperaturea nd thus its effect is not observed in the 13 CM AS spectra.O nt he other hand, the signalathigherppm shows two different resonances (64.3 and 65.8 ppm) at high temperatures, which then coalesce and merge into one as the temperature is lowered.T he coalescence temperature is around 293 Ka nd an activation energy of 58.4 kJ mol À1 evaluated by line shape analysisi sobtained.…”
Section: Resultsmentioning
confidence: 99%
“…This is duet ot he well-known fast rotation of the DABCO unit alongi ts pseudo-three-fold axis, which is associated with av ery low activatione nergy. [30][31][32] Such motion cannotb e frozen at the lowest achievable NMR temperaturea nd thus its effect is not observed in the 13 CM AS spectra.O nt he other hand, the signalathigherppm shows two different resonances (64.3 and 65.8 ppm) at high temperatures, which then coalesce and merge into one as the temperature is lowered.T he coalescence temperature is around 293 Ka nd an activation energy of 58.4 kJ mol À1 evaluated by line shape analysisi sobtained.…”
Section: Resultsmentioning
confidence: 99%
“…NMR relaxation measurements and lineshape analysis of 2 H NMR are among the most powerful methods for elucidating the reorientation frequencies and the trajectories of the mobile elements. A lot of research has been carried out in this respect . For example, the groups of Schurko and Loeb designed a macrocyclic rotaxane “molecular rotor” that rotates on the linkers of a MOF designated as UWDM‐1 .…”
Section: Interfaces In Supramolecular and Hybrid Assembliesmentioning
confidence: 99%
“…Prack et al indicated that variable‐temperature (VT) 2 H SSNMR can provide direct and convincing evidence for a rotating H–Pt–H unit in the Pt‐deuterated complex trans ‐D 2 Pt(Pt t Bu 3 ) 2 . Lineshape analysis of quadrupolar‐echo 2 H NMR measurements in crystalline molecular rotors self‐assembled by halogen bonding of diazabicyclo[2.2.2]octane and a set of fluorine‐substituted iodobenzenes by Catalano et al indicated rotational trajectories consistent with the 3‐fold or 6‐fold symmetric potential of the rotator . The dynamics of central phenylene, branch phenylenes, and peripheral phenyls selectively in crystalline and amorphous molecular rotors were studied by Jiang et al Lineshape analysis of the spectra reveals that the central phenylene, the six branch phenylenes, and the 18 periphery phenyls all display megahertz rotational dynamics in the crystals at ambient temperature.…”
Section: Interfaces In Supramolecular and Hybrid Assembliesmentioning
confidence: 99%
“…A series of analogous trimers {dabco assembled with fluorine‐substituted iodobenzenes, malonate (dabco:malonate = 2:1), [HN(μCH 2 CH 2 ) 3 NH][OOC(HC=CH)COOH] 2 } are all formed by short hydrogen bonds , . Their I–H ··· N hydrogen bond lengths are 2.79 Å on average in the literature, whereas N–H ··· O hydrogen bond lengths are 2.713(1) Å and N–H ··· O hydrogen distances are 2.662(3) and 2.614(4) Å in reference. But they do not undergo any phase transition.…”
Section: Resultsmentioning
confidence: 99%